Role of Duplex Color Doppler Study of Uterine Artery in the Early Diagnosis of Preeclampsia in Pregnant Women (Journal of Medicine, 2019)
Background: Duplex Colour Doppler Sonography is gaining increasing popularity for assessment of blood vessels in various disease processes around the world as well as for the surveillance of fetus compromised by intra uterine growth retardation (IUGR) and to assess foetal structural abnormalities and complex disease processes.Materials & methods: This cross sectional study was carried out to observe Doppler wave form in subjects with preeclampsia enrolling 40 subjects with preeclampsia, in the Department of Radiology and Imaging, Dhaka Medical College Hospital, Dhaka, over a period of six months from 20th May 2012 to 19th November 2012. A total number of 40 normal pregnancies were also included for comparison. Peak systolic velocity (PSV), end diastolic velocity (EDV), Resistive index (RI), Pulsatility index (PI) in different groups of study subjects from 24th to 37th weeks were observed and compared for any significant differences.Results: Majority (35% in normal and 37.5% in preeclampsia) of the respondents were found in the age group of 21-30 years. Unpaired t-test revealed no significant difference between mean age between two groups. Among normal group, mean±SD PSV, EDV, PI and RI were 43.94±15.41 cm/sec and 15.51 (±4.93) cm/sec, 1.12±0.0846 and 0.571 (±0.058) respectively. Mean PSV, EDV, PI and RI were 83.19±18.44 cm/sec, 11.86±5.19 cm/sec, 2.497±0.369 and 0.8255±0.087 in preeclampsia group. There was statistically significant (By unpaired ttest) difference in mean Doppler indices between these two groups. It was observed that early diastolic notch was found in 90% subjects with preeclampsia. Early diastolic notch was observed in Doppler wave form in 5% subject with normal pregnancy. Chi-square test showed that there was statistically significant difference in presence of early diastolic notch between normal subjects and subjects with preeclampsia.Conclusions: From the study result it was concluded that Doppler indices with presence of early diastolic notch are reliable indicators for early detection of preeclampsia.J MEDICINE JUL 2019; 20 (2) : 87-91